ANALYSIS OF INFLUENCE OF NUMERICAL MESH DENSITY ON RESULTS OF SIMULATION OF VON KARMAN VORTEX STREET - Czapla, Beata; Rząsa, Mariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper includes numerical studies of simulating the von Karman vortex street. Knowledge of the vortex street is an important consideration in the design of vortex flowmeters. One of the important elements of the numerical simulation is suitable computational mesh. The paper presents the results of numerical analysis of the effect of mesh density on the simulation result. In numerical calculations a big impact on the correctness of results has the right to prepare a model for the calculation in terms of choice of mesh density. It has been shown that the density of the mesh affects the quality of the results. However be optimum number of elements of mesh, for which further increasing of its elements does not significantly improve results of simulation. In the paper presents the optimal numerical values for the exemplary vortex generator.